THE EFFECT OF THE PREDICT OBSERVE EXPLAIN (POE) LEARNING MODEL ON FACE-TO-FACE LEARNING (F2F) ON THE UNDERSTANDING OF SCIENCE CONCEPTS: IN THE FOURTH GRADE OF ELEMENTARY SCHOOL STUDENTS - Efrillita Sampurno; Fitria Wulandari (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2023)
The purpose of this research to find out the effect and how much influence thelearning model had on predicting and learning the effect of face-to-facelearning on understanding science concepts. This research method usesquantitative experiments a type of the study Quasi Experimental Design andthe form design used is a nonequivalent control group design. The resultsindicated that hypotheses should be tested and problem statements answered,the analysis data techniques use were the Independent Sample T Test and theN-Gain test. You can tell by looking at the average when given treatment usedthe learning model POE in the Post-test to get an average value of 76.49 forthe experimental class and 61.36 for the control class. From the results of theIndependent Samples T Test post-test scores for the experimental and controlclass, namely 2.721 > 1.67 then, H0 is reject and H1 is accept, indicated thatthere is an influence and results of NGain experimental class give POE modelindicated that is a big influence so that it can be use as a learning model. Theconclusion in this study is it learning model POE in face-to-face learning ispositive and significant effect understand concepts science for fourth gradeelementary school student, so that it can be used as a solution in learningscience at elementary school.